Efficient Synthesis of Unsymmetrical Sulfamides via a Lossen‐Like Rearrangement. Issue 12 (24th May 2016) - Pantaine, Loïc; Richard, François; Marrot, Jérôme; Moreau, Xavier; Coeffard, Vincent; Greck, Christine
Abstract: A convenient one‐pot synthesis of unsymmetrical sulfamides via a Lossen‐like rearrangement is reported. The protocol operates under simple conditions at room temperature and does not require an inert atmosphere and a dry solvent. The ability of N‐ hydroxy arenesulfonamide O ‐derivatives to generate under mild conditions N ‐sulfonylimine intermediates was a trigger point for developing a general synthetic strategy towards unsymmetrical sulfamides. The synthetic potential of the methodology has been investigated by preparing cyclic sulfamides and new potential chiral organocatalysts. Abstract :